Reaching to compromise between needs of man and nature - Lewandowski , Karol (Studia Ecologiae et Bioethicae, 2004)
The article has exhibited that ecoengineering, consisting of the scheduled transformation of ecological systems is an alternate and equivalent method for handling natural environment in contrary to environmental technology, which consists of ecosystems protection against human activity. The human activity in the natural environment may consist of devastating, transforming, or protection trials. In a frame of protection (environmental technology) are attempts on limiting anthropopression, which means the influence of man on the natural environment by various restrictions - technological, legal, and ethical. Up to now transforming natural environment was considered as a necessary evil, connected with the technological impossibility to avoid anthropopression or political necessity to satisfy human needs. The attention of researchers engaged in human activities in the natural environment was focused on criticizing of destruction and diverse propositions to stop this destruction, mainly by protectoral actions. Transforming the environment by man was generally considered a part of the destruction process. So there were trials of counteractions or tolerating it as unavoidable, trying to diminish their effect on the natural environment. Positive possibilities connected with planned and system ie transformation of the natural environment were not noticed, especially possibilities of achieving a compromise between human and nature needs. That such a compromise is possible is proving described there in detail examples of Konin lakes and Biebrza swamps. Ecoengineering conception presented in this dissertation generally values up environment transforming, that therefore is a no more necessary evil but becomes an equivalent and alternate action to environment technology (nature protection). Justification of this thesis is achieved by the demonstration that actions limited to environment technology only can be equally destructive for the environment as out of control wastewaters and pollution dumping. This is demonstrated in the article by an example of Sudety forests, devastated by acid rains and the problem of increasing deficit of sulfur in the soil, caused by introducing Sulphur removing from waste gas technology on a mass scale. The article has exhibited that absolute separation of industrial activity from the natural environment is not possible, that is total anthropopression eliminating. Speaking colloquially closing „anthropopression dragon" in a hermetic cave and draw only consumer satisfaction is not possible. Unavoidable is anthropopression connected with emissions of different forms of energy (heat, noise, electromagnetic fields) and matter (steam, carbon dioxide, wastes) and physical biotopes transforming. The only way in this situation is to incorporate anthropopression sources into ecosystems and turn wastes into fertilizers using ecoengineering. To this goal are tending eventually activities realized in frames of Pure Production and environment managing system according to ISO 14001, propagated today as balanced development conception, and diverse forms of so-named active protection, that can be considered as not fully conscious, limited ecoengineering. More, subsequent operations in environmental technology, from that every one eliminates negative effects of previous, are giving ecoengineering effects too, that is including human activity into the natural environment and creation of new, unstable ecological balances. An example can serve discussed in the article sequence of environment technologies: dust removal - desulphurization - production and distribution of sulphuric fertilizers. Method of such „successive environment technologies approximating to eco-engineering" is however much more costly and dangerous form an and nature than could be preamplified ecoengineering practice, what was pointed out too. The ethical basis for ecoengineering could be the principle „we have the right to be there". The biggest transformation of our planet's environment was the replacement of the atmosphere from oxygen-free to oxygenated realized by blue-green algae (Cyanophyta). There is no cause to regard human rights as lesser than algae rights. The author of the article has no intention to claim that ecoengineering is better and more perfect practice than environment technology, who therefore should withdraw and be neglected. Ecoengineering as proceeding equivalent and alternative to environment technology should be considered as equal in every situation where a given ecosystem is influenced by anthropopression. Therefore in this dissertation ecoengineering is not discussed individually but in contact with environment technology as „alternative ecoengineering". Only by considering and deciding about ecoengineering alternatives we can choose the more appropriate method of handling with the natural environment. The author assumes that this is the only method that makes possible correct environment evaluation and selection of the best possible technology. Ecoengineering conception based on creating unstable biological balances, formulated as an ecoengineering alternative is significant, new contribution to systems sozology and other philosophical disciplines connected with ecological problems - philosophy of nature, philosophy of technology, and ecophilosophy and ecological ethic. That situation creates a wide perspective for farther researches, primarily connected with the elimination of one-sided environment technology from sozology, ecophilosophy, and environmental ethics and next creating ethical rules Environment transforming. It seems that ecoengineering may give significant research impulse for the philosophy of technology, which will intensify conceptions of valuating technology, today criticized. Extensive possibilities for researches are connected with precision and developing aspects diverse of ecoengineering as interdisciplinary and system ie science, that in this dissertation, focused on motivating ecoengineering could be signaled only. Ecoengineering can be currently utilized in engineers and designers practice and in environment evaluating system s, provided that corresponding procedures and research methods are created within detailed sciences. There are existing also wide possibilities to explore, discover, and research spontaneous ecoengineering effects, that so far have escaped researchers' notice. Similar site surveys can be run in other parts of Poland or other lands. Therefore yielding conclusions can lead to significant theoretical revaluation and substantially change existing engineering and legal practice. The main research problem is ecosystem modeling for ecoengineering needs. Ecoengineering is a new chance for humanity and nature.